Crystal structure of 4-chloro-N-[2-(piperidin-1-yl)ethyl]benzamide monohydrate - K. Prathebha; D. Reuben Jonathan; B. K Revathi; S. Sathya; G. Usha (Acta Crystallographica Section E: Crystallographic Communications, 2015)
In the title compound, C14H19ClN2O2·H2O, the piperdine ring adopts a chair conformation. The dihedral angle between the mean plane of the piperidine ring and that of the phenyl ring is 41.64 (1)°. In the crystal, molecules are linked by O—H...N, N—H...O and C—H...O hydrogen bonds involving the water molecule, forming double-stranded chains propagating along [010].